The educational role of intellectual awareness units in Saudi universities in achieving intellectual immunity for its students - Asiri, Retal Muhammad (Journal of Educational and Psychological Sciences, 2023)
The study identifys the educational role of intellectual awareness units in achieving intellectual immunity from the point of view of Saudi university students, and its obstacles. It used the descriptive survey method on a sample of (750) students from five Saudi universities; (Tabuk, Hafr Al-Batin, Princess Noura, King Khalid, and Umm Al-Qura), the society of the study is the whole Saudi Arabia universities which the numbers more over 261961 students. The results showed that the educational role of the intellectual awareness units and obstacles to activating this role in achieving intellectual immunity among students from their point of view came to a medium degree, and there were no statistically significant differences at the level of significance (α<0.05) in the research personnel’s responses in the variable of academic specialisation and the university, while there were differences according to the variable of sex. There were no statistically significant differences at the level of significance (α<0.05) in the responses of the research personnel to the obstacles in the variables of sex and academic specialisation, while differences were found in the university variable. It recommended intensifying preventive programs to prevent students from slipping into extremist ideas and increasing the effectiveness of these programs through developing the soft skills of Intellectual knowledge team.